2020
DOI: 10.1128/msphere.00593-20
|View full text |Cite
|
Sign up to set email alerts
|

Daily Vaginal Microbiota Fluctuations Associated with Natural Hormonal Cycle, Contraceptives, Diet, and Exercise

Abstract: ABSTRACT The microorganisms of the vaginal tract are critical for vaginal and reproductive health. However, the regulation of these microorganisms is not well understood. Therefore, we investigated whether different factors regulate the vaginal microbiota of healthy college-aged women (n =26) with high temporal resolution by collecting daily self-administered vaginal swabs and using 16S rRNA sequencing for bacterial identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 67 publications
7
133
1
Order By: Relevance
“…It has previously been reported that host genetics, ethnicity, hormonal stage (e.g. menstruation cycle, menopause, pregnancy), sexual behaviour, and hygiene practices, amongst others factors, influence vaginal microbiota composition [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that host genetics, ethnicity, hormonal stage (e.g. menstruation cycle, menopause, pregnancy), sexual behaviour, and hygiene practices, amongst others factors, influence vaginal microbiota composition [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Song et al longitudinally characterized the vaginal microbiota of healthy young women (Song et al, 2020 ) and showed that vaginal microbial diversity increased and Lactobacillus abundance decreased during menses. The use of hormonal contraceptives disrupted these cyclical changes, suggesting that that temporal variation correlates with the known effects of estradiol on VMB composition.…”
Section: Determinants Of Vaginal Microbiota Compositionmentioning
confidence: 99%
“…Others include sexual intercourse, hormonal contraception, antimicrobial agents, use of lubricants, and vaginal douching, but they have less impact than menstrual periods and cause changes in the vaginal microbiota for a shorter duration ( Gajer et al., 2012 ; Mitchell et al., 2012 ). In addition, in a few women, the vaginal CST does not change with the menstrual cycle and hormonal contraception, but further study by future researchers is needed to determine whether it is related to the metabolic function of bacteria ( Gajer et al., 2012 ; Song et al., 2020 ).…”
Section: Normal Vaginal Microenvironmentmentioning
confidence: 99%
“…Female genital tract infections mainly include vaginitis, cervicitis, and PID ( Sherrard et al., 2018 ). The main cause is exogenous pathogen interference or endogenous dysbiosis ( Workowski and Bolan, 2015 ; Song et al., 2020 ). At present, the relevant research on infectious diseases caused by the interaction between reproductive tract microorganisms, metabolites and the host is mainly focused on BV, Chlamydia trachomatis ( C. trachomatis ), and AV ( Ceccarani et al., 2019 ).…”
Section: Common Reproductive Tract Infectionsmentioning
confidence: 99%